2022
DOI: 10.1021/acscatal.2c02911
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Organization of Photocatalysts and Enzymes on Janus-Type DNA Nanosheets for Efficient CO2 Conversion

Abstract: Bioinspired photosynthetic systems composed of photocatalysts and enzymes are a notable framework for converting CO2 to high-value chemicals. However, catalyst/enzyme deactivation and poor electron transfer kinetics in multistep photochemical processes severely limit their catalytic efficiencies. In this study, Janus-type DNA nanosheets (NSs) presenting two different DNA sequences on each face were utilized as a support for the selective immobilization of a Rh complex and formate dehydrogenase (FDH) for concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…1,2 So far, the prevalent CO 2 reduction methods include photocatalysis, 3 electrochemical reduction, 4 and biological immobilization. 5 Among them, photocatalysis has attracted much attention as a sustainable, green and cost-effective technique. It has been widely applied in various catalytic reactions such as CO 2 conversion, 6 pollutant degradation, 7 water splitting, 8 and nitrogen fixation.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 So far, the prevalent CO 2 reduction methods include photocatalysis, 3 electrochemical reduction, 4 and biological immobilization. 5 Among them, photocatalysis has attracted much attention as a sustainable, green and cost-effective technique. It has been widely applied in various catalytic reactions such as CO 2 conversion, 6 pollutant degradation, 7 water splitting, 8 and nitrogen fixation.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, FDH‐catalyzed CO 2 reduction has been a significant target application in the area of biomimetic CO 2 remediation by harvesting solar energy using photoenzymatic systems [225] . One of the most impressive recent works in this regard has been reported by Fard et al., where the authors demonstrated photoenzymatic CO 2 reduction to formate using TEOA as the reductant [226] . The most ingenious aspect of this study was the spatial compartmentalization of immobilized FDH and an Rh complex on Janus type DNA nanosheet, which had two different DNA sequences on each side, enabling face‐selective immobilization of the FDH and the Rh catalyst to avoid mutual inactivation.…”
Section: Photocatalytic Regeneration Methodsmentioning
confidence: 99%
“…[225] One of the most impressive recent works in this regard has been reported by Fard et al, where the authors demonstrated photoenzymatic CO 2 reduction to formate using TEOA as the reductant. [226] The most ingenious aspect of this study was the spatial compartmentalization of immobilized FDH and an Rh complex on Janus type DNA nanosheet, which had two different DNA sequences on each side, enabling face-selective immobilization of the FDH and the Rh catalyst to avoid mutual inactivation. Based on the amount of formate produced, the TN cofactor reported was 1360, which, to the best of our knowledge, is the highest among photoenzymatic cofactor regeneration studies to date.…”
Section: Photoregeneration Of the Reduced Cofactor 14-nadhmentioning
confidence: 99%
“…[3] Currently, the commonly employed CO 2 reduction methods encompass photocatalytic reduction process, electrochemical reduction, and biological immobilization. [4][5][6] Photocatalytic technology, inspired by plant photosynthesis, utilizes light to convert CO 2 into hydrocarbon fuels. This approach holds several advantages including environmental friendliness, mild reaction conditions, and low cost.…”
Section: Introductionmentioning
confidence: 99%